The high rate of road accidents in Malaysia: What the causative factors are? - Ismail, Nurul Husna; Aziz, Zulkufli (2012)
Road accidents become one of the crucial social problems over the world. The number of accidental death worldwide became the third largest after HIV/AIDS and TB, approximately with 0.8 million of deaths per year.In Malaysia, road accident is become one of major problem with high rate of road accident occurrences.This paper attempts to review the present status of road accidents in Malaysia and what the causative factors are.This paper uses an overview of previous road accidents statistic in Malaysia, the total numbers of casualties, and data of registered vehicles